Role of TWEAK/Fn14 signalling pathway in lupus nephritis and other clinical settings (2017)
ABSTRACT: Knowledge of the signalling pathways involved in various diseases has enabled advances in the understanding of pathophysiological, diagnostic and therapeutic models of several inflammatory and autoimmune diseases. Systemic lupus erythematosus is a widely studied autoimmune disease that can affect multiple organs, with a major impact on morbidity and mortality when it involves the kidneys. Over the past 10 years, interest in the role of the TWEAK/Fn14 signalling pathway in lupus nephritis, as well as other clinical settings, has increased. By reviewing the literature, this article assesses the role of this pathway in lupus nephritis, underlines the importance of TWEAK in urine (uTWEAK) as a biomarker of the disease and stresses the favourable results published in the literature from the inhibition of the TWEAK/Fn14 pathway as a therapeutic target in experimental animal models, demonstrating its potential application in other settings. Results of ongoing clinical trials and future research will give us a better understanding of the real benefit of blocking this pathway in the clinical course of several conditions.